¿Puede la gestión forestal mitigar los efectos de un incremento de sequía en los montes mediterráneos? El caso de los bosques de encina y roble en el contexto del cambio climático. - COTILLAS, M; ESPELTA, J M; Sabate, S (V Congreso Forestal Español, 2009)
Uno de los grandes retos para la conservación de los ecosistemas forestales a lo largo del presente siglo es el cambio climático, del que se esperan importantes repercusiones en la cuenca mediterránea. Los modelos climáticos proyectan para esta área un descenso en la precipitación que, unido a un aumento de las temperaturas, acrecentará la ya de por sí característica sequía estacional que caracteriza esta zona. Dadas estas proyecciones, se hace necesario determinar los efectos que tendría una reducción de la precipitación en las diferentes especies que componen nuestros bosques, para poder así estimar posibles cambios en la estructura y composición de los mismos e identificar estrategias de gestión adecuadas para mitigar su efecto. En este contexto, el objetivo de nuestro estudio es analizar los efectos de una reducción de la precipitación en el monte bajo de encina (Quercus ilex L.) y roble (Quercus cerrioides Willk & Costa), así como evaluar los efectos de la gestión (resalveo) en su respuesta a este. Para ello, se combinan en un bosque mixto dos niveles de precipitación (precipitación natural vs. reducción de la precipitación de un 15%) y gestión (no gestión vs. gestión) en cuatro tratamientos. Se analiza la mortalidad, crecimiento, nueva rebrotada y dinámica foliar. Tras cuatro años de seguimiento el experimento sigue en curso, y hasta ahora se han obtenido los resultados definitivos de mortalidad, crecimiento y nueva rebrotada, que muestran que: i) La gestión reduce fuertemente la mortalidad, ii) El crecimiento de los robles se ve notablemente afectado por la reducción de precipitación, mientras que el de las encinas permanece constante, iii) La gestión incrementa fuertemente el crecimiento en ambas especies, especialmente en condiciones de precipitación natural. Actualmente se están comenzando a analizar los datos de dinámica foliar, y los resultados preliminares muestran que iv) Las parcelas sometidas a reducción de precipitación presentan un número menor de hojas, una menor longevidad de las mismas, y una mayor tasa de caída de hojarasca que las no sometidas a este tratamiento, v) La gestión atenúa la caída de hojas en todas las parcelas, mitigando los efectos de la reducción de precipitación en las parcelas sometidas a este tratamiento. De estos resultados se extrae la conclusión de que el cambio climático puede tener consecuencias negativas sobre los bosques de Quercus mediterráneos, siendo más acusados los efectos en robles caducifolios. Sin embargo, la gestión forestal puede ser una potente herramienta para mitigar estos efectos y conservar nuestros bosques de cara al futuro.
Keywords: cambio climático; Quercus cerrioides; Quercus ilex; resalveo; sequía

Effects of a nursery CO 2 enriched atmosphere on the germination and seedling morphology of two Mediterranean oaks with contrasting leaf habit - Cortés, Pilar; ESPELTA, J M; Save, Robert; Biel, C (New Forests, 2004)
The use of an enriched CO2 atmosphere in tree nurseries has been envisaged as a promising technique to increase productivity and to obtain seedlings with a higher root/shoot ratio, an essential trait to respond to water stress in Mediterranean-type ecosystems. In that framework, we have analyzed the effects of three levels of atmospheric CO2 concentration (350, 500 and 700 ppm) on the germination rate, growth and morphology of seedlings of two Mediterranean oaks used in reforestation programs: the evergreen Quercus ilex L. and the deciduous Quercus cerrioides Wilk. et Costa. CO2 enrichment increased the germination rate of Q. cerrioides (from 70 7 to 81 3%) while it decreased that of Q. ilex (from 71 10 to 41 12%). Seedlings of both species increased approximately 60% their total biomass in response to CO2 enrichment but at two different CO2 concentrations: 500 ppm for Q. cerrioides and 700 ppm for Q. ilex. This increase in seedlings biomass was entirely due to an augmentation of root biomass. Considering germination and biomass partitioning, an enriched CO2 atmosphere might not be appropriate for growing Mediterranean evergreen oaks, such as Q. ilex, since it reduces acorn germination and the only gains in root biomass occur at a high concentration (700 ppm). On the other hand, a moderate CO2 enrichment (500 ppm) appears as a promising nursery technique to stimulate the germination, growth and root/shoot ratio of deciduous oaks, such as Q. cerrioides
Keywords: Forest restoration; Mediterranean-type ecosystems; Nursery techniques; Quercus cerrioides; Quercus ilex; Wildﬁre

Land use changes, natural regeneration patterns, and restoration practices after a large wildfire in NE Spain: Challenges for fire ecology and landscape restoration - ESPELTA, J M; Rodrigo, a; Habrouk, A; Meghelli, N; Ordonez, J L; RETANA, J (FIRE AND BIOLOGICAL PROCESSES, 2002)
Great wildfires have recently affected sub-Mediterranean areas of central Catalonia (NE Spain). The large extension of the burned areas, as well as the fact that non-fire-prone vegetation has been severely affected, lead to ponder over the natural regeneration patterns occurring, and over the best strategies to restore and manage the burned areas. In the present study, we review the land use changes and the natural regeneration patterns observed after the large wildfire that occurred in Bages-Bergueda in 1994. The fire resulted in: (i) the creation of new croplands and pastures in previously forested areas, (ii) the expansion of mixed oak (Quercus ilex and Q. cerrioides) coppices, (iii) the failure of natural regeneration of the dominant tree species (Pinus nigra), leading to the appearance of areas without any tree regeneration. In this context, we discuss the results of different experiments carried out to reforest P nigra stands and to ameliorate the structure of mixed oak coppices.
Keywords: land use changes; Mediterranean areas; natural regeneration; Spain; wildfires

Constraints and trade-offs in Mediterranean plant communities: The case of holm oak-Aleppo pine forests - Zavala, M A; ESPELTA, J M; RETANA, J (The Botanical Review, 2000)
In this paper we review those aspects that are relevant to the development of a mechanistic ecological theory to account for the structure and dynamics of Mediterranean forests, focus- ing our attention on mixed forests of holm oak (Quercus ilex L.), a shade-tolerant, slow- growing species that resprouts vigorously after disturbance, and Aleppo pine (Pinus halepen- sis M.), a fast-growing, nonresprouting, shade-intolerant species. The main objectives of this report are: to introduce some of the primary features of these forests, showing their structural complexity and historical peculiarities; to show that much of this complexity can be concep- tually reduced to two main factors of variation, soil-moisture gradients and a complex inter- action of historical management and disturbance regimes; and to contrast the unique features of Mediterranean systems with other communities that have inspired generalization in ecol- ogy. Plants in Mediterranean-climate regions must face several environmental constraints dur- ing their life cycle: water limitation, competition for light, and a complex set of disturbance regimes, mainly fire, herbivory, and human exploitation. The response of co-occurring spe- cies to a given set of environmental constraints depends on a combination of physiological and morphological traits. In holm oak-Aleppo pine forests, the lower limit of distribution along a soil-moisture gradient appears to be controlled by dry-season water stress on seedling performance, and the upper limit seems to be controlled by shade tolerance relative to com- petitors. The processes that generate and maintain these patterns are related to the responses of the two species to the water and light environments that result from interacting gradients of disturbance and resource availability. The dynamics of mixed holm oak-Aleppo pine forests may be represented along two major environmental axes: water availability and light intensity; namely, time since last disturbance. At the regional scale, the presence of holm oak and Aleppo pine is expected to be driven mainly by the precipitation regime, with the proportion of Aleppo pine in- creasing toward the driest border and with holm oak being the dominant species in areas with higher precipitation. Changes of dominance of holm oak and Aleppo pine also re- spond to water availability at the local scale. In this case, variations between species de- pend on different factors in a complex way, because reduced soil-moisture levels may re- sult either from low precipitation or from topography and edaphic features. The dynamics of holm oak-Aleppo pine forests are also determined by temporal changes in canopy clo- sure; that is, forest recovery after disturbance. In this case, the proportion of Aleppo pine would increase in recently disturbed stands (i.e., with high light intensity reaching the for- est floor), whereas regeneration of holm oak would be dominant under partially closed canopies. Theories of forest dynamics developed in humid regions may apply only poorly to Medi- terranean plant communities, where vegetation change is qualitatively or quantitatively dif- ferent. Thus, succession in temperate forests appears to be driven by differences in light availability and shade tolerance; but in Mediterranean plant communities, water limitation is of greater importance for the distribution of forest species. In Mediterranean landscapes the interaction of life-history strategies with changing environments is difficult to infer from observational and experimental studies. A mechanistic approach, in which competi- tion or plant performance is measured as a function of resource availability, seems more feasible. The idea should be to develop multispeeies models calibrated specifically for Mediterranean forests in a combined program of modeling, field research, and experimenta- tion.
Keywords: Aleppo pine; disturbance regimes; forest dynamics; holm oak (voyant); light intensity; mediterranean plant-communities; Water availability

SUPERVIVENCIA DE PLANTULAS DE PINO CARRASCA (PINUS HALEPENSIS) y ENCINA (QUERCUS ILEX) EN BOSQUE MIXTOS DE AMBAS ESPECIES - ESPELTA, J M; RETANA, J; Gené, C; Riba, M (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
In this paper, survival of holm oak and Aleppo pine seedlings in holm oak stands, Aleppo pine stands and mixed stands, both in cut and uncut plots, is analized. Survival of holm oak seedlings in uncut plots is greater than that of Aleppo pine seedlings in the three types of forest considered. Mortality of seedlings of both species in 9ut plots is considerably smaller than that of uncut plots. K.W.:
Keywords: Aleppo pine; Holm oak; mixed forest; Seedling; survival curve